ANALISIS TERJEMAHAN BAHASA PERANCIS PADA NOVEL PERBURUAN KARYA PRAMOEDYA ANANTA TOER - Miyondri, Popi (Universitas Pendidikan Indonesia, 2017)
This article reveals the results of this analyze the translation into French language of novel Perburuan by Pramoedya Ananta Toer. This novel has chosen as our resource of this research because this novel has won the BalaiPustaka award in 1949 in Jakarta and this novel describes the ideology of the people in Indonesia and Japanese colonizer in Japanese colonization period. This study was conducted to answer our two questions, such as how translator translates the novelPerburuan and is the translator is a faithful translator or unfaithful translator?. This study is based on qualitative research by analyzing the translation of title, book cover and also the phrases translated which has indicated a translation style of French translator.we analyze this data by using the theories of translation such as post-colonial translation theory and cultural translation theory for third word countries as our references to analyze the novel translated intitledLe Fugitif by François-René Daillie. The results of this study are the translator is a faithful translator based on the contexte and content in the novel Perburuan. The style of faithful translation aims to convey the author’s intention as faithfully as possible into original version to the French readers.Keywords: Translation, language, novel, post-colonial translation, cultural translation